1991
DOI: 10.1002/cne.903130211
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism of mechanoreception in Ruffini endings in the periodontal ligament of hamster incisors

Abstract: The topographical relationship between Ruffini endings and the surrounding collagen fibers in the periodontal ligament of hamster incisors was investigated by means of both immunohistochemistry for neurofilament protein (NFP) and electron microscopy. Periodontal Ruffini endings, a type of stretch receptor, were present exclusively in the alveolar half of the periodontal ligament. Their axon terminals were densely and regularly associated with transverse collagen fibers, possibly forming a mechanoreceptive comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…The predominant type of nerve ending in the dog periodontal ligament was shown in the present study to be the thick type of tree-like ending without any specialized terminal structures such as capsules or lamellae. Their distribution and intimate relationship with collagen fibers remind us of the Ruffini endings in rodent periodontal ligament (SATO et al, 1988(SATO et al, , 1989KANNARI, 1990;KANNARI et al, 1991). Their shape, In comparison with the rodent type, the dog-type of Ruffini ending is represented by a tree-like profile, less repeatedly branching and not remarkably swollen at the end of each branch.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The predominant type of nerve ending in the dog periodontal ligament was shown in the present study to be the thick type of tree-like ending without any specialized terminal structures such as capsules or lamellae. Their distribution and intimate relationship with collagen fibers remind us of the Ruffini endings in rodent periodontal ligament (SATO et al, 1988(SATO et al, , 1989KANNARI, 1990;KANNARI et al, 1991). Their shape, In comparison with the rodent type, the dog-type of Ruffini ending is represented by a tree-like profile, less repeatedly branching and not remarkably swollen at the end of each branch.…”
Section: Discussionmentioning
confidence: 97%
“…The electron microscope study by BYERS (1985) first reported the existence of Ruffini endings, a type of stretch receptor which is predominant in the collagenous tissues, in the periodontal ligament of rat molars. Recently, our research group demonstrated an extremely rich distribution of Ruffini endings in the periodontal ligament of rodents (SATO et al, 1988(SATO et al, , 1989KANNARI, 1990;KANNARI et al, 1991). In these studies, immunohistochemical techniques enabled us to visualize the entire configuration of Ruffini endings in molars of rats (MAEDA et al, 1987) and in the incisors of all rodents examined (SATO et al, 1988(SATO et al, , 1989KANNARI, 1990;KANNARI et al, 1991): the endings repeatedly branched in a dendritic fashion, each terminal twig being expanded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations